2023
DOI: 10.3390/toxins15020086
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Group Study on the Effect of OnabotulinumtoxinA in Patients with Chronic Migraine Associated with Medication Overuse Headache: Pain Catastrophizing Plays a Role

Abstract: Pain catastrophizing and cutaneous allodynia are commonly altered in patients with chronic migraine associated with medication overuse headache (CM-MOH) and tend to improve in parallel with clinical improvement. The relation between pain catastrophizing and cutaneous allodynia is poorly understood in patients with CM-MOH receiving OnabotulinumtoxinA therapy. In this single-arm open-label longitudinal observational study, patients with CM-MOH were assigned to structured withdrawal and then administered Onabotul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Our results on ASC-12 parallel those of a previous work on BoNT-A of our group, whose population included the subset of BoNT-A patients of the RAMO study from the Milan centre [41]. Conversely, other studies showed that BoNT-A in CM can be effective by influencing central sensitisation, by modulating nociceptive drive, and by reducing the overall burden of migraine [32], and the ASC-12 score decreased significantly in a similar treated population [42,43].…”
Section: Discussionsupporting
confidence: 84%
“…Our results on ASC-12 parallel those of a previous work on BoNT-A of our group, whose population included the subset of BoNT-A patients of the RAMO study from the Milan centre [41]. Conversely, other studies showed that BoNT-A in CM can be effective by influencing central sensitisation, by modulating nociceptive drive, and by reducing the overall burden of migraine [32], and the ASC-12 score decreased significantly in a similar treated population [42,43].…”
Section: Discussionsupporting
confidence: 84%
“…In this context, having patients become aware of improving pain scores after treatment can have positive reinforcement, in line with the encouraging findings obtained by adding acceptance and commitment therapy to the standard of care [54]. Interestingly, in patients treated with OBT-A, a reduction in pain catastrophizing significantly predicted a decline in headache frequency [55].…”
Section: Discussionmentioning
confidence: 56%